The Acoustic Impedance of a Vibrating Annular Piston Located on a Flat Rigid Baffle Around a Semi-Infinite Circular Rigid Cylinder - RDZANEK, Wojciech P.; RDZANEK, Witold J.; PIECZONKA, Dawid (Archives of Acoustics, 2012)
The axisymmetric problem of acoustic impedance of a vibrating annular piston embedded into a flatrigid baffle concentrically around a semi-infinite rigid cylindrical circular baffle has been undertaken inthis study. The Helmholtz equation has been solved. The Green’s function valid for the zone consideredhas been used for this purpose. The influence of the semi-infinite cylindrical baffle on the piston’s acousticimpedance has been investigated. The acoustic impedance has been presented in both forms: integral andasymptotic, both valid for the steady harmonic vibrations. Additionally, the acoustic impedances of thepiston with and without the cylindrical baffle have been compared to one another. In the case withoutthe cylindrical baffle some earlier results have been used.